Barriers and Facilitators Implementation of Evidence-Based Nursing practice in Hospitals: A Literature Review - Swito, Ikar; Sidin, Indahwaty (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The results of the literature review study clearly show: that attitudes and beliefs, knowledge about EBP, a capability to interpret faithful journals, nurses' demographic characteristics including the level of education, work experience, and age influenced the implementation of EBP. At the organizational level, the obstacles in implementing EBP consist of facilities and infrastructure, leadership, conflict, group dynamics, workplace, and organizational culture, lack of human resources, workload, lack of time, lack of internet access, the need for role models in the implementation of EBP. The results clearly showed that the implementation of evidence-based practice was a complex structure where the support of both individuals and organizations was very influential. It was necessary at the individual level to increase knowledge and skills in implementing EBP. However, workplace organizational management and strategic support integrated into the hospital's vision became the initial capital in implementing EBP